Novel presentation of rigid flat foot flexor hallucis longus passing through the subtalar joint: A comprehensive case report - Mohammad Alkhreisat, MD; Khairat Battah, MD; Osama Aldahamsheh, MD; Mohammad Alananzh, MD; Omar Ababneh, MD; Iyad Farouji, MD (Radiology Case Reports, 2024)
This case report presents a novel cause of rigid flatfoot caused by the entrapment of the Flexor Hallucis Longus (FHL) tendon within the subtalar joint. A 19-year-old male with chronic right ankle and foot pain diagnosed with rigid flatfoot deformity. MRI identified the FHL tendon entrapped within the subtalar joint, a condition to our knowledge never previously reported. This report highlights the importance of thorough clinical evaluation and advanced imaging techniques in diagnosing rare causes of rigid flatfoot and suggests that surgical options may still be valid for such rare presentations.